2017
DOI: 10.1177/1403494817705558
|View full text |Cite
|
Sign up to set email alerts
|

Subjective health complaints and exposure to peer victimization among disabled and non-disabled adolescents: A population-based study in Sweden

Abstract: Disabled adolescents report poorer health and are more exposed to both traditional bullying and cyber harassment. This public health issue needs more attention in schools and in society in general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…However, a study reveals a connection between such punishments and being an aggressor (20) . This study also confirms the previous data which established that a risk factor for being a victim of bullying is having any type of disability (21)(22) .…”
Section: Discussionsupporting
confidence: 91%
“…However, a study reveals a connection between such punishments and being an aggressor (20) . This study also confirms the previous data which established that a risk factor for being a victim of bullying is having any type of disability (21)(22) .…”
Section: Discussionsupporting
confidence: 91%
“…Bullying is a pervasive peer relationship problem with psychological, social, and academic consequences (Annerback, Sahlqvist, & Wingren, 2014;Barzilay et al, 2017;Fahy et al, 2016;Landstedt & Persson, 2014;Waasdorp & Bradshaw, 2015). Studies have also indicated a possible association between bullying and physical symptoms, such as pain (Fridh, Kohler, Moden, Lindstrom, & Rosvall, 2018;Gini, Pozzoli, Lenzi, & Vieno, 2014) and the use of analgesics (Garmy, Hansson, Vilhjalmsson, & Kristjansdottir, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between disability among children and exposure to bullying is an under researched area. There is no consensus on how to define disability, but children categorised as disabled are more often subjected to victimization compared to non-disabled children [ 12 , 16 , 17 ]. Fridh et al (2017) found disabled adolescents report poorer health and are more exposed to both traditional bullying and cyber harassment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is no consensus on how to define disability, but children categorised as disabled are more often subjected to victimization compared to non-disabled children [ 12 , 16 , 17 ]. Fridh et al (2017) found disabled adolescents report poorer health and are more exposed to both traditional bullying and cyber harassment [ 17 ]. Secondary analysis of other European and Australian general population cohort studies involving younger children also report higher and more persistent rates of mental health and behavioural issues with children with intellectual disabilities compared to their peers without intellectual disabilities [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation